2010
DOI: 10.1128/cvi.00365-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Measurement of Cell-Mediated Immune Responses of Swine to the M and N Proteins of Porcine Reproductive and Respiratory Syndrome Virus

Abstract: The principal objectives of this study were to develop autologous antigen-presenting cells (APCs) and to characterize the antigen-specific T-cell responses to the M and N proteins of porcine reproductive and respiratory syndrome virus (PRRSV) by using those APCs in outbred pigs. The orf6 and orf7 genes fused with porcine granulocyte-macrophage colony-stimulating factor (GM-CSF) were cloned into the mammalian expression vector to generate two plasmid DNAs, namely, pcDNA3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
(62 reference statements)
3
14
0
Order By: Relevance
“…Despite differing MHC class-I and -II haplotypes, T-lymphocytes in gilt 1 and 2 recognized a common epitope-containing peptide (P538) in GP4. Identification of M protein sequences recognized by T-lymphocytes in several previous reports [58,59,62,68] as well as in the current study suggest that M protein is epitope-rich region suitable for inducing T-lymphocytes recognizing diverse PRRSV isolates, particularly since PBMCs have originated from genetically diverse pigs infected with various PRRSV genotypes.…”
Section: Discussionsupporting
confidence: 73%
“…Despite differing MHC class-I and -II haplotypes, T-lymphocytes in gilt 1 and 2 recognized a common epitope-containing peptide (P538) in GP4. Identification of M protein sequences recognized by T-lymphocytes in several previous reports [58,59,62,68] as well as in the current study suggest that M protein is epitope-rich region suitable for inducing T-lymphocytes recognizing diverse PRRSV isolates, particularly since PBMCs have originated from genetically diverse pigs infected with various PRRSV genotypes.…”
Section: Discussionsupporting
confidence: 73%
“…M protein is the most conserved structural protein among PRRSV strains (Kapur et al, 1996;Murtaugh et al, 1998) and it is the main inducer of virus-specific T-cell response (Bautista et al, 1999;Jeong et al, 2010). Our results indicated that M protein was fully stable in rTGEV (see above).…”
Section: Prrsv M Protein As Scaffold For Prrsv Antigenic Domains Exprsupporting
confidence: 55%
“…Neutralizing antibodies against PRRSV are mainly directed to GP5 protein (Kim and Yoon, 2008;Ostrowski et al, 2002), although neutralizing antibodies recognizing GP3 and GP4 have also been described following PRRSV infection (Costers et al, 2010;Oleksiewicz et al, 2002;Vanhee et al, 2011). PRRSV M protein is a potent inducer of T-cell proliferation in piglets infected with PRRSV, and may also play a role in protection (Bautista et al, 1999;Jeong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…T cell proliferation and IFN-␥ synthesis were induced in immunized pigs only in response to M and N, with M being more stimulatory. By contrast, serum antibodies were produced only to N (Jeong et al, 2010). This approach, using T cells and MHC-matched autologous APCs, to identify T cell epitopes is likely to be useful in future studies.…”
Section: Viral Epitope Targets Of T Cell Immunitymentioning
confidence: 99%